Becoming Israeli, becoming Hebrew - sociolinguistic landscapes of Israel - Wodzińska, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present paper scrutinizes the relations between language, nation and state in the context of the Israeli society and its collective identity. A critical approach at a commonly-agreed model is taken and after the analysis of the history and present demographics of Israel, a revised model is suggested.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie